The War Trumpet : Iberian Epic Poetry, 1543-1639 - Blanco, Mercedes, 1953-; Martinez-Osorio, Emiro (Book collections on Project MUSE., 2023)
"The epic poems written during the rise of Portugal and Spain on the global stage often dealt with topics quite unimaginable to the likes of Virgil or Homer. These poems reveal the astounding opportunities for upward social mobility and self-promotion afforded by broader access to print and the vast amount of knowledge and material wealth accrued through maritime exploration. Iberian poets of the period were quite cognizant of their ventures into uncharted territory, and that awareness informed their literary journeys. The War Trumpet features nine substantial essays that expand our understanding of Iberian Renaissance epic poetry by posing questions seldom raised in relation to poems such as La Araucana, Os Lusíadas, Carlo famoso, El Bernardo, Arauco Domado, Espejo de paciencia, and Felicissima Victoria, among others. Particularly compelling are questions concerned with early modern understandings of the natural world, the practice of poetic imitation, the discipline of cartography, or the reception of Petrarchism in the newly established viceroyalties of the New World. Fostering a greater appreciation of the intersection between poetry, war, and exploration, The War Trumpet sheds light on the transformative changes that took place during the period of Iberian expansion."--